Efforts to Improve Long Serve Skills in Badminton through the Demonstration Method: Upaya Meningkatkan Keterampilan Servis Panjang dalam Permainan Bulu Tangkis melalui Metode Demonstrasi - Ramlah Ramlah; Adriana Bulu Baan; Gunawan Gunawan; Rahmayati Rahmayati (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2025)
This Classroom Action Research (CAR) study aims to improve students' long serve skills in badminton for Grade VIII students at SMPN 2 Palu. The problem identified was the low mastery of long serve skills, with only 27% of students meeting the minimum competency criteria in the pre-cycle assessment. The research was conducted in two cycles, each consisting of four stages: planning, action implementation, observation, and reflection. In Cycle I, 70% of students achieved mastery, though 30% did not meet the required standards. After improvements were made in Cycle II, including enhanced visual demonstrations and immediate feedback, significant progress was observed, with 94% of the 33 students achieving mastery. These findings suggest that the demonstration method effectively improves students' long serve skills in badminton by offering clear visual understanding and structured practice opportunities.